Electron Transport at the Nanometer‐Scale Spatially Revealed by Four‐Probe Scanning Tunneling Microscopy. (26th March 2013) - Li, An‐Ping; Clark, Kendal W.; Zhang, X.‐G.; Baddorf, Arthur P.
Abstract Electron transport at the nanometer‐scale is the key to novel applications of nanomaterials in electronic and energy technologies. Due to the restricted dimensionality, one of the distinctive characteristics of nano‐systems is their transport properties critically depend on structural details. Therefore, an important requirement for transport research of a specific nanomaterial system is to examine structures and properties in a coherent manner. In this regard, four‐probe scanning tunneling microscopy (STM), which combines four independently controllable STMs with a scanning electron microscope (SEM) in the same cryogenic environment, is uniquely useful for probing electron transport on multiple length‐scales and revealing how transport is coupled to the electronic and structural properties down to the atomic scale for individual nanomaterials. By utilizing this unique tool, extensive research has been undertaken to explore aspects of nanotransport, which include (a) intertwined electronic and structural phase transitions in surface supported two‐dimensional structures, (b) effects of atomic defects and interwire coupling on the electronic and transport properties of ultra thin quantum wire systems, (c) grain boundary resistances in copper nanowires with one‐to‐one correspondence to the grain boundary structure, (d) defect scattering effects in two‐dimensional electron gas systems, and (e) evaluation of transport behaviors of individual semiconductor nano‐junctions and nanodevices. In this paper, transport measurement techniques are first introduced with a four‐probe STM and then the recent progress on its applications is reviewed with a focus on the spatially resolved electron transport at the nanometer‐scale. The goal is to stimulate further advancement and utilization of techniques capable of characterizing materials properties at the nanometer‐scale to facilitate the exploration of the great promise of nanoscience and nanotechnology.